2009
DOI: 10.1227/01.neu.0000340685.06407.fd
|View full text |Cite
|
Sign up to set email alerts
|

Dose-Related Efficacy of a Continuous Intracisternal Nimodipine Treatment on Cerebral Vasospasm in the Rat Double Subarachnoid Hemorrhage Model

Abstract: Intracisternal nimodipine lavage with 5 microL/hour, but not with 10 microL/hour leads to significant arterial relaxation. Further research is needed to elucidate the underlying cause of the decreasing nimodipine effect at higher dosage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 44 publications
3
14
0
Order By: Relevance
“…[14], [15], [16] For the “double hemorrhage” model, peak angiographic vasospasm and perfusion deficits in this model have been demonstrated to occur on day 5 after induction of SAH. [17] [18] Furthermore the mortality rate in the present study was 26%, which is in line with previous published studies using this hemorrhage model. [17], [19], [20] …”
Section: Discussionsupporting
confidence: 93%
“…[14], [15], [16] For the “double hemorrhage” model, peak angiographic vasospasm and perfusion deficits in this model have been demonstrated to occur on day 5 after induction of SAH. [17] [18] Furthermore the mortality rate in the present study was 26%, which is in line with previous published studies using this hemorrhage model. [17], [19], [20] …”
Section: Discussionsupporting
confidence: 93%
“…An additional 64 studies were excluded after reading the full text because they did not completely fulfill the inclusion criteria or they reported preliminary or incomplete data. Data from 70 papers were then extracted (Bilginer et al, 2009;Bulsara et al, 2006;Caner et al, 1996;Chang et al, 2010;Chen et al, 2009;Cheng et al, 2009;Chung and Lee, 1993;Cosentino et al, 1993;Espinosa et al, 1984;Findlay et al, 1988Findlay et al, , 1989Findlay et al, , 1990Grasso et al, 2002;Gul et al, 2010;Hanggi et al, 2009;Hariton et al, 1993;Hino et al, 1995;Itoh et al, 1993Itoh et al, , 1994Josko et al, 2000;Kanamaru et al, 1990Kanamaru et al, , 1991Kawada et al, 1999;Kawashima et al, 2000;Kim et al, 1996Kim et al, , 2000Kita et al, 1998;Kwan et al, 1997Kwan et al, , 2001Kwan et al, , 2006Laslo et al, 2006;Lewis et al, 1988;Lin et al, 2007;Macdonald et al, 1998aMacdonald et al, , b, 2004Marbacher et al, 2008;Matsui and Asano, 1994;Matsumura et al, 1991;McGirt et al, 2002McGirt et al, , 2006…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the in vivo angiographie dilation of constricted major cerebral arteries by NDP supports the long documented initiator role of a continuously elevated intracellular Ca^+ level in the development of vasospasm [25,26], although mechanisms independent of Ca^+ but related to Rho-kinasemediated Ca^"*" sensation etihancement with ET-1 and OxyHb as upstream stimulators have emerged [27,28], which may partially clarify the weakness of NDP on delayed vasospasm. By means of digital subtraction angiography, Hänggi et al [29] demonstrated the efficacy of intracisternal NDP lavage with 5 /.tL'hour to induce significant arterial relaxation. However, demonstration of the basilar artery, the mostly interfered artery in this model, in response to nimopine treatment was excluded.…”
Section: Discussionmentioning
confidence: 99%